Robust Digital Image Watermarking Against Cropping Using Sudoku Puzzle in Spatial and Transform Domain - shadi saneie (Journal of Intelligent Procedures in Electrical Technology, 2016)
With rapid development of digital technology, protecting information such as copyright, content ownership confirmation has become more important. In image watermarking, information of the image is inserted such that the visual quality of the image is not reduced and the receiver is able to get the required information. Some attacks such as image cropping, destroy the watermark’s information. In this article, a new watermarking scheme is proposed which is robust against tough cropping. In the proposed scheme, classic Sudoku table which is a 9*9 table, has been used. One feature of Sudoku table is that Sudoku's limitations cause uniform scattering of symbols or numbers throughout the table. In the proposed scheme, Sudoku table and both watermarking approaches based on spatial domain and transform domain such as DCT and DWT are used. Lack of using of soduko solution at the stage of extraction and finding correct solution to obtain watermark, is innovation of this scheme. Robustness of watermarking against cropping attack is up to 92%, which shows good and effective performance of the proposed scheme.